Pengaruh Kualitas Produk, Persepsi Harga, dan Brand Image terhadap Keputusan Pembelian dengan Electronic Word of Mouth sebagai Variabel Moderasi (Studi Kasus pada Produk Lipstik Make Over) - Pertiwi, Karina Putri; Yulia, Iis Anisa; Fitrianti, Dewi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study is designed to examine the effect of product quality, price perception, and brand image on the consumer purchasing decision-making process., with Electronic Word of Mouth (eWOM) as a moderating variable. The research sample included all customers of Make Over Lipstick products, with a total of 150 respondents. The data collection method in this study uses non-probability sampling techniques with an accidental sampling approach. Data analysis was carried out through two statistical approaches, namely multiple regression to test the direct relationship and moderation regression analysis to test the interaction effect. The research findings show that: (1) product quality and price perception statistically significantly influence purchasing decisions, (2) brand image does not have a significant impact, and (3) electronic word of mouth (eWOM) acts as a moderating variable that strengthens the effect of product quality and price perception, but is not effective in moderating the relationship between brand image and purchasing decisions.